2021
DOI: 10.21203/rs.3.rs-193370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Virtual Clinic the Way Forward: Patient Satisfaction Comparing Phone Clinic vs. Conventional Clinic

Abstract: Background:Outpatient clinics play a vital role in assessing and treating patients. They traditionally involve face-to-face consultation with a clinician to diagnose and treat many medical and surgical conditions. During the COVID-19 pandemic many of these traditional methods were replaced with telemedicine to minimise patient interaction and therefore potential exposure. This study utilises data from patient questionnaires with the aim of determining patient satisfaction in regard to telemedicine.Method:A lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A study comparing the satisfaction among 100 individuals regarding virtual clinic and telemedicine revealed a high satisfaction score with a mean score of 9.08 out of 10. The study demonstrated that telemedicine continues to develop and become more acceptable among the population [19].…”
Section: Discussionmentioning
confidence: 88%
“…A study comparing the satisfaction among 100 individuals regarding virtual clinic and telemedicine revealed a high satisfaction score with a mean score of 9.08 out of 10. The study demonstrated that telemedicine continues to develop and become more acceptable among the population [19].…”
Section: Discussionmentioning
confidence: 88%
“…Remote consultations are an increasingly used and widely available method of patient consultation, which have demonstrated consistently high satisfaction scores from patients. Remote telephone consultations also reduce the logistical and geographical barriers which may prevent patients from accessing services 26. As the preoperative pharmacist review did not require any direct patient examination, this service was ideally placed to use the benefits of remote consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Remote telephone consultations also reduce the logistical and geographical barriers which may prevent patients from accessing services. 26 As the preoperative pharmacist review did not require any direct patient examination, this service was ideally placed to use the benefits of remote consultations. Our results demonstrate that patients found this method of pharmacist consultation useful and convenient, and that it improved their overall experience of care.…”
Section: Patient Opinionmentioning
confidence: 99%